A control design for a photovoltaic transformerless HB-NPC inverter with leakage-ground current reduction. (March 2023) - Iturriaga-Medina, S.; Martinez-Rodriguez, P.R.; Escobar, G.; Soriano-Rangel, C.A.; Langarica-Cordoba, D.; Vazquez-Guzman, G.; Lopez-Sarabia, J.
Abstract: A control design for an HB-NPC transformerless inverter is presented in this paper, the proposal includes a modified LCL passive output filter which is aimed to attenuate leakage-ground currents in a transformerless photovoltaic generation system. This modification consists of a simple connection of the filter capacitors to the positive and negative nodes of the DC-link. A theoretical analysis of the differential-mode and common-mode models is performed. Thus, the proposed control law is designed in these new variables of the system. Therefore, the proposed control law consists of two main loops, an inner control loop which is based on the differential-mode model, and a DC-link voltage balance control loop based on the common-mode model. The current tracking loop features a proportional gain plus a bank of resonant filters to enhance the tracking on the differential-mode current reference. The common-mode voltage loop features a PI controller aimed to guarantee the DC-link common-mode voltage regulation objective. To assess the performance of the proposed solution a 1 kW experimental setup of the H-bridge neutral-point clamped transformerless inverter is used with the proposed LCL filter and controller. Highlights: The HB-NPC topology with modified LCL filter for LGC reduction in TL-PVS is analized. DMM and CMM, used in the control design, give a better understanding of the LGC behavior. The controller guarantees both power injection to the grid and capacitors' voltage balance. The experimental evaluation shows the effectiveness of the proposed solution.